2017
DOI: 10.4085/1062-6050-52.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nintendo Wii Balance Board as a Tool for Measuring Postural Stability After Sport-Related Concussion

Abstract: Context: Recent changes to postconcussion guidelines indicate that postural-stability assessment may augment traditional neurocognitive testing when making return-to-participation decisions. The Balance Error Scoring System (BESS) has been proposed as 1 measure of balance assessment. A new, freely available software program to accompany the Nintendo Wii Balance Board (WBB) system has recently been developed but has not been tested in concussed patients.Objective: To evaluate the feasibility of using the WBB to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Of course, the authors still think that kinesio taping has positive effects, such as improving the performance of the ankle [18]. Second, Nintendo Wii Fit Plus is a tool for VR, but it was created for entertainment [19]. For example, it is difficult to set muscle strength and balanced exercise time accurately in this equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the authors still think that kinesio taping has positive effects, such as improving the performance of the ankle [18]. Second, Nintendo Wii Fit Plus is a tool for VR, but it was created for entertainment [19]. For example, it is difficult to set muscle strength and balanced exercise time accurately in this equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging, portable, inexpensive, and valid system for the quantitative assessment of human movement could represent a worthy resource for clinician and researchers. Previous studies have addressed validity and reliability of the Wii Balance Board (WBB) for assessing the kinetic characteristics of lower-limb movements (Abujaber, et al, 2015;Yamamoto & Matsuzawa, 2013) and the standing balance (Clark, et al, 2010(Clark, et al, , 2017Pagnacco, et al, 2010;Park & Lee, 2014;Pavan, et al, 2015;Sañudo, Rueda, del Pozo-Cruz, de Hoyo, & Carrasco, 2016;Sgrò, et al, 2014) in comparison with the goldstandard force plate (FP). Almost all studies found the WBB to be valid for the afore-mentioned aims but recommended to pay more attention to use WBB and FP interchangeably.…”
Section: Discussionmentioning
confidence: 99%
“…The WBB is a plate composed of four transducers that are used to acquire the forces provided above the board's surface. This device has already been compared with the gold standard force plates in terms of its usage feasibility and inter-and intra-device validity (i.e., in comparison with FPs and with the same WBB, respectively) for assessing postural control abilities (Clark, et al, 2010;Clark, Mentiplay, Pua, & Bower, 2018;Huurnink, Fransz, Kingma, & van Dieën, 2013;Merchant-Borna, et al, 2017;Pagnacco, Oggero, & Wright, 2010;Park & Lee, 2014;Pavan, Cardaioli, Ferri, Gobbi, & Carraro, 2015;Sgrò, Monteleone, Pavone, & Lipoma, 2014). Studies about intradevice reliability showed intra-class correlation coefficients ranging from poor to excellent, while inter-device validity was found excellent if the same posturography parameters were acquired from the plates.…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts can be divided into two main approaches: postural sway and error scoring [ 14 , 17 ]. The first has been evaluated by using force plate [ 17 , 18 , 19 ] or wearable devices [ 14 , 20 , 21 ]. Different from the scores of BESS, the metrics of postural sway are quantified by measured changes in body sway amplitude, velocity, frequency and direction of anterior-posterior, medial-lateral or trunk-rotation movements [ 20 ].…”
Section: Introductionmentioning
confidence: 99%